Oxygen therapy reduces secondary hemorrhage after thrombolysis in thromboembolic cerebral ischemia - Sun, Li; Zhou, Wei; Müller, Christian; Sommer, Clemens; Heiland, Sabine; Bauer, Alexander T.; Marti, Hugo; Veltkamp, Roland (Journal of cerebral blood flow & metabolism, 2010)
Hyperbaric oxygen (HBO) and normobaric hyperoxia (NBO) protect the brain parenchyma and the cerebral microcirculation against ischemia. We studied their effect on secondary hemorrhage after thrombolysis in two thromboembolic middle cerebral artery occlusion (MCAO) (tMCAO) models. Beginning 60 minutes after tMCAO with either thrombin-induced thromboemboli (TT) or calcium-induced thromboemboli (CT), spontaneously hypertensive rats (n=96) breathed either air, 100% O2 (NBO), or 100% O2 at 3 bar (HBO) for 1 hour. Immediately thereafter, recombinant tissue plasminogen activator (rt-PA, 9 mg/kg) was injected. Although significant reperfusion was observed after thrombolysis in TT-tMCAO, vascular occlusion persisted in CT-tMCAO. In TT-tMCAO, NBO and HBO significantly reduced diffusion-weighted imaging-magnetic resonance imaging (MRI) lesion volume and postischemic blood-brain barrier (BBB) permeability on postcontrast T1-weighted images. NBO and, significantly more potently, HBO reduced macroscopic hemorrhage on T2* MRI and on corresponding postmortem cryosections. Oxygen therapy lowered hemoglobin content and attenuated activation of matrix metalloproteinases in the ischemic hemisphere. In contrast, NBO and HBO failed to reduce infarct size in CT but both decreased BBB damage and microscopic hemorrhagic transformation. Only HBO reduced hemoglobin extravasation in the ischemic hemisphere. In conclusion, NBO and HBO decrease infarct size after thromboembolic ischemia only if recanalization is successful. As NBO and HBO also reduce postthrombolytic intracerebral hemorrhage, combining the two with thrombolysis seems promising.